HEADLINE DAN SUBHEADLINE DALAM WACANA IKLAN KATALOG PRODUK KECANTIKAN ORIFLAME: PELANGGARAN MAKSIM DAN IMPLIKATUR - Yogyanti, Devita; Atiqah, Annisa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Advertising has to be made as attractive as possible to boost product sales. There are many ways to create attractive advertising content, one of which is by creating headlines and subheadlines with captivating language. One of the companies that managed to write headlines and subheadlines with captivating language is Oriflame, a cosmetics company from Sweden. Oriflame's product advertising headlines and subheadlines use the maxim violation to create compelling implicatures. This study aimed to analyze the maxim violation and how the implicature resulted from the maxim violations. This research used descriptive qualitative methods and interpretation methods in determining implicature. The result showed that copywriters violate all the maxims, namely maxim of quality, quantity, relevance, and manner . Metaphor, personification, sinekdoke and alusion is applied to violate maxim of manner. Implicature resulting from the maxim violation is then freely translated by the consumer. The message tried to tell in Oriflame's advertising implicature was in the form of ideas about femininity and beauty that are popular among women. That's what made women easily capture the implicature so that they are interested in buying their products.